Analysis of the Implementation of the Family Planning and Reproductive Health (KBKR) Program in Minimizing Stunting in Padang Pariaman Regency - Faula Zhafirah; Putri Febri Wialdi (Darul Yasin Al Sys, 2026)
Stunting remains a major public health challenge in Indonesia, prompting the implementation of multisectoral interventions, including the Family Planning and Reproductive Health (KBKR) Program. Padang Pariaman Regency constitutes a priority area because of persistent constraints related to healthcare access, human resource availability, and public understanding of contraception. This study aims to analyze the implementation of the KBKR Program in supporting stunting reduction and identify the factors influencing its implementation in Padang Pariaman Regency. A qualitative descriptive approach was employed, with informants purposively selected from the Population Control and Family Planning Agency, the Health Office, Ketaping Community Health Center, healthcare workers, and community members. Data were collected through observations, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the KBKR Program has been implemented relatively well based on the Mazmanian and Sabatier policy implementation framework, encompassing independent, intervening, and dependent variables. Program implementation is supported by clearly defined objectives, cross-sectoral coordination, and implementers’ commitment to delivering community-based services. Nevertheless, implementation remains suboptimal because of limited public understanding of contraception, shortages of trained personnel, inadequate operational funding, geographical barriers to service accessibility, and insufficient community participation. The study concludes that the effectiveness of the KBKR Program in supporting accelerated stunting reduction depends on strengthening implementers’ capacity, increasing budgetary support, expanding equitable access to services, and providing continuous public education. These findings contribute to public policy and health-program implementation studies by demonstrating the importance of institutional capacity, service accessibility, and community engagement in integrating family planning and reproductive health interventions with stunting-reduction efforts.